2020
DOI: 10.1055/a-1107-3058
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cytotoxicity, Pharmacokinetics, and Excretion Properties of Sapindoside B from the Seeds of Nigella sativa var. hispidula

Abstract: The seeds of Nigella sativa var. hispidula are widely used in food preparation by the Uighur people in western China. Recently, series of oleanane triterpenoid saponins were extracted from the seeds of Nigella sativa var. hispidula, especially α-hederin as representative that exhibited strong antitumor activity. Compared to α-hederin, sapindoside B has just 1 more terminal xylopyranose in the 3-O position and displays similar effects against various human cancer cell lines with cisplatin. Considering this pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For example, N. glandulifera and TSN were con rmed to exhibit signi cant antioxidant and anti-in ammatory properties (Zhao et al 2013;Zheng et al 2020). Triterpene saponins are the dominant group of anti-in ammatory compounds existed in this ethnomedicinal plant (Hu et al 2014;Hu et al 2020) and Nigella A was a major ingredient of triterpene saponins extracted from N. glandulifera. Nigella A was 60.36 ± 1.25 g/100 g total saponins of N. glandulifera (Zhao et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, N. glandulifera and TSN were con rmed to exhibit signi cant antioxidant and anti-in ammatory properties (Zhao et al 2013;Zheng et al 2020). Triterpene saponins are the dominant group of anti-in ammatory compounds existed in this ethnomedicinal plant (Hu et al 2014;Hu et al 2020) and Nigella A was a major ingredient of triterpene saponins extracted from N. glandulifera. Nigella A was 60.36 ± 1.25 g/100 g total saponins of N. glandulifera (Zhao et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The content of Nigella A was 60.36 ± 1.25 g/100 g existed in TSN (Zhao et al 2013). Our previous results revealed that saponins were the principal active components of N. glandulifera with the highest content (64.5%) and Nigella A (also named Sieboldianoside A) is a major oleanane triterpenoid saponin isolated from N. glandulifera (Hu et al 2020;Zheng et al 2020). We speculated that it could be used to treat a variety of in ammation-related diseases by regulating ora and immune.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…As many saponins exhibit pharmacological properties, a review of the absorption, disposition, and pharmacokinetics of saponins had been done [79]. Recently, the pharmacokinetics and excretion studies of sapindoside B in rat were conducted and reported the pharmacokinetic profiles of sapindoside B in the range of 2.5 to 12.5 mg/kg dosage-dependently, and only 2% intravenous dose of sapindoside B was excreted in its parent form over 48 h [80]. More research is needed to explain the contradiction between the low bioavailability of saponins and their potential anticancer activity in vivo.…”
Section: Discussionmentioning
confidence: 99%